The "Chinese style reforms" and the Hungarian "Goulash Communism" - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, 2009)
Similarities and differences will be demonstrated between Chinese and Hungarian party-state systems. We define the role of reforms in the self-reproduction of both party-states. We shall demonstrate how different patterns of power distribution lead to the implementation of different reforms. We shall describe how these different reforms have created the Hungarian Goulash communism and the Chinese style reforms. We shall also explain the conditions that have lead Goulash communism to political transformation first in Hungary accompanied by economic crisis, and Chinese style reforms to economic transformation first in China, accompanied by macroeconomic growth.
Keywords: B52; D85; N10; P2; P3; P41; P52; 330; reforms; transformation; party-state systems; goulash communism; Chinese style reforms; Politisches System; Macht; Politische Reform; Wirtschaftsreform; Vergleich; China; Ungarn